Spontaneous ascitic fluid infection and bacteremia due to Yersinia pseudotuberculosis in a liver transplant patient. (May 2015) - Renvoisé, A.; Lemaitre, N.; Saintenoy, G.; Benosman, H.; Geffrier, C.; L. Epelboin,; Jarlier, V.; Poynard, T.; Thabut, D.
Highlights: We report a bacteremic ascitic fluid infection caused by Y. pseudotuberculosis . This infection has been rarely reported. The outcome was not favorable using ciprofloxacin as treatment. The outcome was favorable after a third-generation cephalosporin and gentamicin. Abstract: We report herein a case of bacteremic ascitic fluid infection in a liver transplant patient caused by a strain of Yersinia pseudotuberculosis serogroup I that lost the yersiniabactin core. The patient's outcome was favorable after a combined therapy with a third-generation cephalosporin and gentamicin.